Optimalisasi strategi pemasaran untuk meningkatkan penerimaan peserta didik baru di SMP Islam Ma’arif 02 Malang - Zaida, Prifti Nensi Fira (Maliki Interdisciplinary Journal, 2024)
The sustainability of an educational institution is greatly influenced by public interest, so schools must be able to build a good image and reputation. To achieve this, effective marketing efforts are needed. Marketing includes more than just efforts to introduce the school, but also aims to instill a feeling of belonging to the school, so that it can build strong relationships between the school and stakeholders. This research aims to find out and describe marketing strategies in increasing the acceptance of new students at SMP Islam Ma'arif 02 Malang. This research method uses descriptive qualitative research. Data collection techniques use interviews, observation and documentation, by describing facts in the field and then continuing with analysis. The research results show that the marketing strategy carried out at SMP Islam Ma'arif 02 Malang uses promotions. Regarding promotions, schools distribute brochures and calendars. Apart from that, it also holds competition events every new year. This year it is an elementary school level competition, as well as utilizing social media to carry out promotions. By introducing the existing programs at SMP Islam Ma'arif 02 Malang, this school applies the Islamic style of AHLUSSUNAH WAL JAMAAH (Aswaja) where the Aswaja lesson is a value that must be instilled in students within the Nahdlatul Ulama Educational Institution.